Peranan Kompetensi Pedagogik Guru dan Keaktifan Belajar Siswa pada Mata Pelajaran IPS melalui Pembelajaran dalam Jaringan di SMP N 2 Cepiring Kendal - Sari, Tri Wulan; Hermanto, Fredy (Sosiolium: Jurnal Pembelajaran IPS, 2021)
The aim of the research of this study was to determine the pedagogical competence of social studies teachers and student learning activeness in the social studies learning process and social studies teacher schools through online learning at SMP N 2 Cepiring Kendal. The results showed that the social studies teacher at SMP N 2 Cepiring Kendal has an important role in student learning activeness by continuing to implement the pedagogical components of the teacher that they must have, including the ability to master student material, the ability to master learning theory, the ability to develop curriculum theory, master potential abilities. learners, and take advantage of information and communication technology. The activeness of students in the learning process can be seen from the ability of students to capture learning material which can be seen from various things such as listening, discussing, and expressing opinions during the teaching and learning process.